Isoflurane-lipid emulsion injection as an anticonvulsant and neuroprotectant treatment for nerve agent exposure - Jishnu K. S. Krishnan; John R. Moffett; Narayanan Puthillathu; Erik A. Johnson; Aryan M. Namboodiri (Frontiers Media S.A., 2024)
We have shown that briefly inhaled isoflurane rapidly halts convulsions and protects the central nervous system (CNS) from organophosphate-induced neuronal loss when administered at 5% for 5 min, even as late as 1 h after organophosphate exposure. In the current study we investigated if an injectable form of isoflurane was as effective as inhaled isoflurane. We used a mixture of 10% isoflurane dissolved in an IV-compatible lipid-water emulsion for intravenous administration. Rats with an implanted jugular vein cannula were infused with 1,000 μL of the 10% isoflurane-lipid emulsion (ILE) mixture at a rate of 200 μL per minute, which achieved full anesthesia lasting approximately 10 min. When administered 30 min after a highly lethal dose of the organophosphate insecticide paraoxon (POX), the short-duration administration halted convulsions over the course of the study and prevented the great majority of neuronal loss as shown by Fluoro-Jade B staining (FJB). Our results indicate that injectable isoflurane is very effective for treating organophosphate poisoning, negating the need for vaporizer equipment and enabling intravenous therapy.